Invented traditions, forced unions. The case of bolivian salteña and Coca Cola - Calvimontes Díaz, Vanessa (Revista de Historia Social y de las Mentalidades, 2025)
Bolivian gastronomy is distinguished by having a great and varied offer of street food, considered a fundamental part of society. Among the dishes offered, salteña is one of the most representative foods, not only for its history and exquisite flavor, but also for the way in which it has been appropriated by a transnational company such as Coca Cola, which tries to create a “gastronomic tradition” between carbonated and this special type of empanada. This article questions this forced link through an interview with experts, a popular consultation through a survey and the analysis of the last marketing campaign carried out by the company
Keywords: Appropriation; tradition; street food; Coca Cola